Welfare, employment, and hours of work - Axel Hall; Gylfi Zoega (Kiel Institute for the World Economy (IfW), 2019)
The authors propose an explanation of why Europeans choose to work fewer hours than Americans and also suffer higher rates of unemployment. Labor market regulations, unemployment benefits, and high levels of public consumption in many European countries reduce, ceteris paribus, the gains from being employed, which makes employed workers ask for higher wages relative to productivity. The higher wages make firms offer fewer vacancies, as well as raising the level of consumption enjoyed by workers, which makes them want to enjoy more leisure because consumption and leisure are complements in the utility function.
Keywords: J63; J64; J65; 330; job search; unemployment; working hours